TANGGUNGJAWAB PELAKU USAHA DALAM PENJUALAN GAS LPG 3 KG YANG BERMASALAH MENURUT UNDANG-UNDANG PERLINDUNGAN KONSUMEN: Responsibility of Business Actors in the Sale of Problematic 3 Kg LPG Gas According to the Consumer Protection Law - Sumaragatha, I Gusti Bagus Sakah; Evangelista, Beverly; Mulyana, Septira Putri (Ganec Swara, 2025)
The problem that arises in the use of LPG gas is that the gas cylinder can burst due to problems, one example is a leaking LPG cylinder. This study aims to determine the responsibility of business actors in the sale of problematic 3KG LPG gas according to the Consumer Protection Law. Normative research method using conceptual approach and statutory approach. The results of the research The responsibility of business actors (agents and bases) is to provide compensation, compensation and / or replacement if the goods and / or services received or utilized are not in accordance